Aplikasi Piranti Lunak Penganalisis Sintaksis Kalimat Bahasa Indonesia - Yusuf, Sablin (Bina Nusantara University, 2011)
Indonesian has a vast variety in structures and sentence types that brings about difficulty in using the language correctly and accurately. This research aims for producing a software application for syntax analysis and error checking for Indonesian sentences. The method used in developing the application is rapid prototyping method which consists of several phases: system requirement analysis, design, coding, implementation and evaluation while the method used in syntax analysis process is regular expression and predictive parsing method. Despite some existing limitations, the application produced is able to check the syntax error of various Indonesian sentence types.